Adolescent and expressions of school discontent: cases study - Carneiro, Cristiana; Souza, Lívia Tedeschi Rondon de; Coutinho, Luciana Gageiro; Silva, Raisa de Paula Fernandes da (Clinical Styles. The Journal on the vicissitudes of childhood, 2016)
The article aims to present a study based on two adolescents’ cases both forwarded from school to a psychiatry service. The research makes a link between psychoanalysis and educational areas. Methodology used is research-intervention, which allowed us to classify the material collected in 2013 and 2014 in order to analyze their results, that have been listed into thematic categories and subcategories extracted from the adolescents’ speeches. In conclusion, the challenges in education are produced by multiple factors, not only individual ones, which juxtaposes contemporary logic of educational problems medicalization